Mapping Research on Problem Based Learning (PBL) in Elementary School Science Learning - Ita Maulana Zakiyah (FASHLUNA, 2025)
The PBL learning model in science lessons is a solution to improve critical thinking skills, learning motivation, and improve student learning outcomes in the current era. This study aims to provide in-depth information about the research of the PBL model in science learning in elementary schools, especially on the research method, focus of the study, and the theme of the study. The method used is SLR (systematic literature review). Data collection was carried out by documentation and reviewing articles about the PBL learning model in science lessons in the period 2020-2025. The data were collected from 40 articles in Google Scholar and Sinta. The results of the study show that the Based Learning learning model uses various methods, namely qualitative, quantitative, mixed methods, and research and development. The most popular method is qualitative while the least popular method is research and development. This study examines the focus of problems grouped into three, namely the impact on learning outcomes, student motivation, and student critical thinking. The results of this study indicate that most research studies on the PBL model focus on the impact on student learning outcomes, while the fewest studies discuss the impact of the PBL model on student motivation.